Membentuk Generasi Tangguh: Sinergi P5 dan Penguatan Pendidikan Karakter dalam Membangun Disiplin Siswa Sekolah Dasar - Damayanti, Gina; Sri Dewi Nirmala; Anggy Giri Prawiyogi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the relationship between character education programs—namely the Pancasila Student Profile Strengthening Project (P5) and the Strengthening of Character Education (PPK)—and the disciplinary behavior of elementary school students in the Cikole District. The method used was a correlational quantitative approach with a population consisting of sixth-grade students and classroom teachers in the Cikole District. The sample included 266 students and 117 teachers selected using random sampling techniques. The instruments used for data collection were questionnaires and interviews. The results showed that: 1) there is a relationship between P5 and students' disciplinary behavior with a significance value of 0.016 and a correlation strength of 0.223 (indicating a weak relationship); 2) there is a relationship between Strengthening of Character Education and students' disciplinary behavior with a significance value of 0.013 and a correlation strength of 0.229 (indicating a weak relationship); and 3) there is a relationship between P5 and Strengthening of Character Education combined with students' disciplinary behavior, with a significance value of 0.029 and a correlation strength of 0.246 (indicating a weak relationship). In conclusion, there is a significant yet weak relationship between P5 and Strengthening of Character Education and the disciplinary behavior of elementary school students. Keywords: Character education, Disciplinary behavior, P5